Sociology of Religion: A Reader - Mirola, William (Routledge, 2018)
Cover -- Half Title -- Title -- Copyright -- Contents -- Preface -- Introduction -- Section I Changing Contexts -- 1 America's Changing Religious Landscape: Overview -- 2 Changing American Congregations: Findings from the Third Wave of the National Congregations Study -- 3 All Creatures Great and Small: Megachurches in Context -- 4 "Nones" on the Rise: One-in-Five Adults Have No Religious Affiliation -- 5 Is the United States a Counterexample to the Secularization Thesis? -- 6 The Gender Gap in Religion Around the World: Women are Generally More Religious Than Men, Particularly Among Christians -- 7 Gendering Secularization Theory -- 8 Socioeconomic Inequality in the American Religious System: An Update and Assessment -- 9 The Shifting Religious Identity of Latinos in the United States: Nearly One-in-Four Latinos Are Former Catholics -- 10 The Impact of International Migration on Home Churches: The Mar Thoma Syrian Christian Church in India -- 11 Redefining the Boundaries of Belonging: The Institutional Character of Transnational Religious Life -- 12 Religious Population Share and Religious Identity Salience: Is Jewish Identity More Important to Jews in Less Jewish Areas? -- Section II Evolving Content -- 13 Spiritual but Not Religious?: Beyond Binary Choices in the Study of Religion -- 14 "I Was a Muslim, But Now I Am a Christian": Preaching, Legitimation, and Identity Management in a Southern Evangelical Church -- 15 Warrior Chicks: Youthful Aging in a Postfeminist Prosperity Discourse -- 16 The Embodied Goddess: Feminine Witchcraft and Female Divinity -- 17 U.S. College Students' Perception of Religion and Science: Conflict, Collaboration, or Independence? A Research Note -- 18 Sensing God: Bodily Manifestations and Their Interpretation in Pentecostal Rituals and Everyday Life -- Section III Patterning Diversity